European innovation scoreboard 2004 : comparative analysis of innovation performance - European Commission. Enterprise Directorate-General (Enterprise and Industry publications, 2005)
Executive summary (s. 4-6).
Keywords: innovaatiot : EU-maat; Euroopan unioni : innovaatiot